Hyobanche hanekomii (Orobanchaceae), a New Species from the Western Cape of South Africa. - Wolfe, Andrea D. (Phytotaxa, 2018)
The new species Hyobanche hanekomii is described and illustrated. It is somewhat intermediate in appearance between H. sanguinea and H. atropurpurea, but can be distinguished from both in several morphological characters that are presented. The new species occurs in the Cape Fold Belt Mountains of the northwest part of the Western Cape.